Nuclear control of respiratory chain expression by transcriptional activators and coactivators - Scarpulla, Richard (Henry Stewart Talks, 2007)
Contribution of nuclear and mitochondrial genomes to respiratory chain expression, Genomic origin of respiratory chain subunits, Cytochrome c as a model for respiratory gene expression, DNA binding and transcriptional properties of nuclear respiratory factors (NRF-1 and NRF-2), Identification and characterization of NRF target genes, Phenotypes associated with a targeted disruption of NRF-1 in mice, NRF control of mitochondrial transcription factor expression, The PGC-1 family, PRC functional interactions with NRF-1 and CREB, Cytochrome c promoter occupancy by PRC during the transition from quiescence to proliferative growth, Potential role for PRC in integrating mitochondrial functions with cell growth
Archived at 2019/06/30